Why do Farmers not Use Fertilizer? A Case of Multistorey Cropping System with Abaca under Coconut in Zamboanga Peninsula, Philippines - Aladin Repaso; Raquel Salingay; Zabdiel Zacarias; Myrna Pabiona; Maria Estela Detalla; Ma. Stella Paulican (Turkish Journal of Agriculture: Food Science and Technology)
The Zamboanga Peninsula region significantly contributes to the Philippine coconut production, wherein abaca is also cultivated as an additional crop within coconut plantations. Still, coconut farmers belong to the country’s poverty sector. Abaca plays a significant role in providing an alternative source of income as a perennial intercrop in agroforestry systems like coconut. However, the productivity and sustainability of this farming system are affected by practices such as nutrient management, which is not explicitly known. Using a mixed-methods approach, this study applies a combination of quantitative and qualitative data-gathering techniques to assess the nutrient management practices adopted by the 33 qualified respondents, including challenges encountered and perceptions to abaca under the coconut farming system and fertilizer use. Quantitative data were analyzed using IBM SPSS Statistics version 29, and thematic analysis was utilized for qualitative data. Results indicate that most (88%) of the farmers in the area did not apply fertilizers for their abaca. Yet, they still consider abaca as one of the income-generating crops besides coconut. The lack of financial resources and irregular harvesting operations are significant challenges that hinder fertilizer application. Findings revealed the need to develop low-cost and practical nutrient management technology for abaca under coconut, which shall be complemented with an effective human resource management system of skilled harvesters for the continuous harvesting operation of abaca to translate good crop growth into good yield and income. This will serve as a basis for government institutions and other stakeholders in developing and implementing programs and policies to improve the abaca and coconut industries.